Protective Effects of Melatonin on Saccharomyces cerevisiae under Ethanol Stress - Mercè Sunyer-Figueres; Albert Mas; Gemma Beltran; María-Jesús Torija (MDPI AG, 2021)
During alcoholic fermentation, Saccharomyces cerevisiae is subjected to several stresses, among which ethanol is of capital importance. Melatonin, a bioactive molecule synthesized by yeast during alcoholic fermentation, has an antioxidant role and is proposed to contribute to counteracting fermentation-associated stresses. The aim of this study was to unravel the protective effect of melatonin on yeast cells subjected to ethanol stress. For that purpose, the effect of ethanol concentrations (6 to 12%) on a wine strain and a lab strain of S. cerevisiae was evaluated, monitoring the viability, growth capacity, mortality, and several indicators of oxidative stress over time, such as reactive oxygen species (ROS) accumulation, lipid peroxidation, and the activity of catalase and superoxide dismutase enzymes. In general, ethanol exposure reduced the cell growth of S. cerevisiae and increased mortality, ROS accumulation, lipid peroxidation and antioxidant enzyme activity. Melatonin supplementation softened the effect of ethanol, enhancing cell growth and decreasing oxidative damage by lowering ROS accumulation, lipid peroxidation, and antioxidant enzyme activities. However, the effects of melatonin were dependent on strain, melatonin concentration, and growth phase. The results of this study indicate that melatonin has a protective role against mild ethanol stress, mainly by reducing the oxidative stress triggered by this alcohol.